A vision-based dual-modal system for adjusting the orientation and plant spacing of ginger with biharmonic depth completion and rapid hand–eye calibration - Shuxiang He; Lin Liu; Yihe Zhang; Jin Cheng; Yuhua Li; Jialin Hou; Rui Hou; Kai Zhou (Computers and Electronics in Agriculture, 2026)

Devonian subduction polarity reversal in the southern Altaids: Evidence from the Central Tianshan Arc, Eastern Tianshan–Beishan Orogenic Belt - Kai Wang; Wenjiao Xiao; Shoufa Lin; Wenhua Ji; Qigui Mao; Miao Sang; Zhihua Wang; He Yang; Qinxiang Zhang (Lithos, 2026)

Nicotine-induced mitophagy in bronchial epithelial cells and MYST1 downregulation in cigarette smoke–exposed lungs: potential mechanisms of COPD progression - Kai Liu; Dongchuan Xu; Jie Zhao; Rubing Mo; Mei Lin; Chanyi He; Qi Lin; Tian Xie; Quanni Li; Yipeng Ding (Molecular Biology Reports, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Hericium erinaceus polysaccharide–chitosan oligosaccharide hydrogels: Rheological insights and application as novel probiotic carriers - Jian Wang; Yifan Lin; Ahsan Hafiz Muhammad; Liang He; Liang Gao; Bangwei Ye; Peilong Sun; Yongjian Chen; Kai Yang (Food Research International, 2026)

Computational, pharmacokinetic and wastewater-based evidence for persistent carbamazepine metabolites and their ecological risks in municipal wastewater treatment plants - Kai He; Jinlong Yuan; Yingchao Lin; Nian Shi; Kexin Tang; Hongyang Wang; Shinya Echigo; Wen Liu (Environmental Pollution, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Effects of taurine on microbiota composition, metabolic profiles, immune capacity, and survival of Manila Clam (Ruditapes philippinarum) larvae - Yang Liu; Kai Liao; Yang Zhang; Qi Hu; Xiaoxue He; Fengjun Xie; Lin Zhang; Zhongming Huo; Jilin Xu (Aquaculture, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Unveiling the Impact of Copper Metabolism on Epithelial-Mesenchymal Transition of Triple-Negative Breast Cancer: Identification of Therapeutic Targets - Kai Zhuang; Lin Yan; Muhammad Waqas; Haixin Feng; Siqi Tang; Haoqi He; Xinshi Yu; Yanling Wang; Zunnan Huang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Direct recovery of silver and simultaneous purification of silicon from end-of-life photovoltaic modules via a one-step hydrothermal method - Danyan Qin; Kai Zhang; Shihao He; Xian Xie; Jie Liu; Long Peng; Yingzhu Li; Di Wu; Yaokai Zhong; Yun Shen; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

Multi-omics profiling complements physicochemical monitoring by revealing functional signatures of dissolved oxygen status in the Xijiang River - Jizhou Cao; Kai He; Xiaohong Chen; Jiabiao Wang; Qidong Yin; Wei Ouyang; Hongyang Wang; Jiachong Lin; Chenguang Fan (Water Research, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Heading control of a multi-fin biomimetic robotic fish based on Q-learning enhanced central pattern generator (CPG) - Qiyang Zuo; Lin Liang; Xinyi Gao; Yiyang Li; Jiazi Geng; Zhengkun Yi; Feifei Zhang; Kai He; Fengran Xie (Ocean Engineering, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The relative roles of cell size and phylogeny in driving dissimilarity of algal functional trait - Qiang He; Bin Chen; Kai-Kai Deng; Peng Yan; Gui-Jiao Lin; Qiu-Wen Chen; You-Peng Chen; Jin-Song Guo (Bioresource Technology, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Machine learning-driven GC–MS analysis for assessing the contribution of amino acids in the flavor of cheese maturing at high temperature - Xinyue Hao; Junzhe Zou; Jianhua Zeng; Jian He; Baolei Li; Kai Lin; Huaxi Yi; Lanwei Zhang; Pimin Gong (International Journal of Food Microbiology, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

From foe to friend: Taming the δ-phase of FAPbI3 for oriented growth and high-performance perovskite solar cells - Xian Xie; Yanzhuo Gou; Kai Zhang; Wei Zhang; Jiaqi Zhang; Jie Liu; Shihao He; Jinhua Li; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Trigger efficient peroxydisulfate-assisted photocatalysis by S-scheme Co3O4/BiOCl heterojunctions: Vital roles of Co2+/Co3+ redox centers and oxygen vacancies - Chang-Bin Yu; Chong Xu; Lin He; Wei-Ya Huang; Kai Yang; Dan Li (Journal of Environmental Chemical Engineering, 2025)

A comprehensive overview of the composition, isolation, purification, and biological activities of abalone polysaccharides - Qing Zhang; Ling Qin; Jiayi Liu; Jinzheng Wei; Junhan Cao; Kai Wang; Mengke Yao; Huan Lin; Yingying He; Changfeng Qu; Jinlai Miao (Food and Bioproducts Processing, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

Factors influencing soil carbon stocks in secondary subtropical forests of eastern China - Hong Lin; Zaihua He; Kai Tian; Xiangshi Kong; Zhaohui Li; Feng Zhou; Xingjun Tian (CATENA, 2025)

Predicting and Optimizing Cotton Yield and Nitrogen-Phosphorus Fertilization Using the DSSAT Model and Ecological Stoichiometry Theory - Zhuo Yu; Meiwei Lin; Yi Chen; Xiaoju He; Kai Lu; Kairui Wen; Weihong Sun; Weiguo Fu (Journal of Soil Science and Plant Nutrition, 2025)

Latitudinal Beta‐Diversity Gradient of Riverine Macroinvertebrate: Interplays of Climatic and Land Use Factors - Ruxia Qiao; Hanrui Wang; Yuqing Lin; Qiuwen Chen; Jianyun Zhang; Kai Chen; Tao Feng; Shufeng He; Hanlu Yan (Global Ecology and Biogeography, 2025)
Aim Climate change and land use have major effects on macroinvertebrate biodiversity, but it is unclear how they shape spatial variations, particularly at large scales. This study explored the latitudinal patterns of beta diversity in riverine macroinvertebrate assemblages and examined how they are shaped by climate and land use. Location China (18°–48° N). Time Period From 2006 and 2021. Major Taxa Studied Riverine macroinvertebrates. Method A comprehensive dataset covering macroinvertebrate taxa from 42 watersheds across China was compiled to explore the latitudinal patterns of taxonomic, functional, and phylogenetic beta diversities, including turnover and nestedness components. Generalised additive models were used to assess the impacts of climatic and land use variables, selected from 20 climatic and 10 land use candidates, on latitudinal patterns of beta diversity. Results Taxonomic and functional beta diversities shared a non‐monotonic latitudinal pattern, minimised at 24°–30° N, contrasting with the monotonic increase in phylogenetic beta diversity. Taxonomic beta diversity was dichotomously regulated by climatic stability and land use: diminishing nestedness in low‐latitude regions while augmenting spatial turnover in high‐latitude regions as latitude increased. For functional beta diversity, climate was identified as an indirect factor influencing historical trait‐pool constraints, whereas land use was identified as a direct factor altering its nestedness component. Phylogenetic beta diversity demonstrated no significant association with contemporary environmental variables. Main Conclusions This study uncovers three facets of macroinvertebrate beta diversity with different latitudinal patterns, highlighting the disparate influences played by climate and land use on these spatial differences as well as the distinct importance of processes causing nestedness and turnover. These insights provide a foundation for latitude‐specific conservation strategies that aim at preserving the macroinvertebrate diversity in rivers.

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

RNA interference targeting cytochrome P450 cyp303a1 on the performance of Henosepilachna vigintioctopunctata - Kai-Yun Fu; Miao He; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2025)

Machine learning and GC–MS revealing the characteristic flavour compounds of Cheddar cheese origin-independent at different ripening periods - Xinyue Hao; Liang Liu; Olayemi Eyituoyo Dudu; Baochao Hou; Weilian Hung; Jian He; Baolei Li; Kai Lin; Huaxi Yi; Lanwei Zhang; Pimin Gong (Food Research International, 2025)

Nutrient availability-driven shifts in nitrogen and phosphorus trade-offs in Microcystis aeruginosa: Understanding cellular resource allocation - Qiang He; Bin Chen; Gui-Jiao Lin; Kai-Kai Deng; Peng Yan; You-Peng Chen; Fang Fang; Jin-Song Guo (Journal of Environmental Management, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Satellite-Based Emission Inversion for Air Pollutants and Greenhouse Gases: A Review - Zhe Jiang; Jintai Lin; Tai-Long He; Fei Jiang; Jianbing Jin; Kai Qin; Lu Shen; Panpan Yang; Zengliang Zang; Lin Zhang; Yuzhong Zhang; Bo Zheng; et al. (Journal of Meteorological Research, 2025)

Spatiotemporal variations and risk assessment of fungicides in the Dongjiang River Basin: Tributaries as contamination hotspots - He Zhang; Wei Ouyang; Kai He; Dongsheng Li; Wenyuan Hu; Yiqi Tian; Xin Hao; Xiuming Sun; Shaoqing Liu; Chunye Lin; Mengchang He (Journal of Hazardous Materials, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhancement of methane production from pig manure by ferrate pretreated anaerobic digestion: Performance and mechanism - Yukai Zheng; Jiarui Wang; Xiaojun Niu; Xintai Su; Xiaoyan He; Yunxia Hu; Dongmei Zhao; Deye Chen; Yu Lin; Kai Li (Chemical Engineering Journal, 2025)

Green solvent hydrothermal recycling of end-of-life crystalline silicon photovoltaic modules - Kai Zhang; Shihao He; Danyan Qin; Xian Xie; Wei Zhang; Pan Deng; Jintao Li; Hongdan Rao; Heming Deng; Tao Mei; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2025)

Regulating organic loading to mitigate the impact of microplastics on nitrogen removal and microbial communities in SBR systems - Yi Yang; Lin Luo; Jian Zhu; Kai Deng; Changjun Li; Ying Zhang; Zhongxiang He; Pofei Wang; Hua Peng (Journal of Water Process Engineering, 2025)

Ferrihydrite enhance performance in anaerobic digestion of pig manure: Methane production, Feammox and metabolic pathway - Yukai Zheng; Jiarui Wang; Xiaojun Niu; Xintai Su; Xiaoyan He; Yunxia Hu; Dongmei Zhao; Deye Chen; Yu Lin; Kai Li (Journal of Water Process Engineering, 2025)

A continental record of Early Cretaceous (Aptian) vegetation and climate change based on palynology and clay mineralogy from the North China Craton - Chang Lu; Miao-Qin Lin; Jun Shen; Xing-Kai Ji; Chuan-Mao Yang; Zhi-Hua Zhang; Qian He; Ming-Dao Sun; Yi-Gang Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

An involvement of a new zinc finger protein PbrZFP719 into pear self-incompatibility reaction - Ying Xu; Zhi-Heng Sui; Yi-Peng Ye; Lei Wu; Kai-Jie Qi; Min He; Lin Guo; Chao Gu; Shao-Ling Zhang (Plant Cell Reports, 2025)

Structure-activity relationship between crystal plane and pyrite-driven autotrophic denitrification efficacy: Electron transfer and metagenome-based microbial mechanism - Yingmu Wang; Shi Chen; Yuanjing Chen; Junge Xu; Jian Zhou; Qiang He; Ziyuan Lin; Kai-qin Xu; Gongduan Fan (Water Research, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Data-driven optimization of nose profiles for water entry impact load reduction - Kai Lv; Enfan Lin; Yongze Liu; Zongbao Chen; Yexian Wang; Ming He; Jiale Yan; Pengyu Lv; Yantao Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2025)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Collagen peptide and taurine synergistically improve hypertensive kidney injury induced by high salt diet through gut-kidney axis - Kai Shen; Shuqi He; WenDa Li; Siyi Song; Qianxia Lin; Huoxi Jin (Food Bioscience, 2024)

Developing water quality and land use surrogates to predict endocrine-disrupting chemical profiles in a highly urbanized river basin - He Zhang; Wei Ouyang; Kai He; Lei Wang; Jietong Pei; Chunye Lin; Shangwei Zhang; Dongsheng Li; Mengchang He; Xitao Liu (Environmental Pollution, 2024)

Granular insights into occupant behaviours and CO2 emissions in the UK - Ruiming Zhang; Tongyu Zhou; Rui Jing; Hua Cai; Tao Lin; Kai Wang; Huanye He; Guoqin Zhang; Xian Wu; Hong Ye (Journal of Cleaner Production, 2024)

Different preferences for inorganic carbon influence CO2 flux under Cyanobacteria or Chlorophyta dominance days - Kai-Kai Deng; Yi-Xuan Li; Peng Yan; Yuan-Chen Huo; Hao Yang; Bin Chen; Qiang He; Gui-Jiao Lin; Jin-Song Guo (Journal of Environmental Management, 2024)

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Impact of nickel and alkaline earth metals interaction on sustainable carbon nanotubes generation from plastic face masks via catalytic pyrolysis - Xiu-Xian Lim; Siew-Chun Low; Kai Qi Tan; Kun-Yi Andrew Lin; Chao He; Tao Zhou; Wen-Da Oh (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Strategies to turn adversity into profits: Potential roles of tetrabromobisphenol a and tetrachlorobisphenol a in promoting carbon sequestration and lipid accumulation in microalgae - Bin Chen; Ping Yang; Peng Yan; Gui Jiao Lin; Qiang He; Kai Kai Deng; Jinsong Guo (Chemical Engineering Journal, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Preservation of shrimp quality using slightly acid electrolysed water combined with grape seed extract: Microbiological and quality analyses with proteomic insights - Yun He; Chenxi Guo; Yi Le; Yi Kai; Lin Chen; Hongshun Yang (Food Bioscience, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Age-associated proteins explain the role of medial temporal lobe networks in Alzheimer’s disease - Adam Turnbull; Yejin Kim; Kai Zhang; Xiaoqian Jiang; Zihuai He; Victor W. Henderson; F. Vankee Lin (GeroScience, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Predicting environmental risks of pharmaceutical residues by wastewater surveillance: An analysis based on pharmaceutical sales and their excretion data - Lihao Pang; Kai He; Yuxuan Zhang; Penghui Li; Yingchao Lin; Junjie Yue (Science of The Total Environment, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Integrating fecal pollution markers and fluorescence analysis for water quality assessment of urban river - Zejun Liu; Jinlong Yuan; Yingying Lin; Feng Lin; Bingjun Liu; Qidong Yin; Kai He; Xinfeng Zhao; Haoxian Lu (Science of The Total Environment, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Meta-analysis of microbial source tracking for the identification of fecal contamination in aquatic environments based on data-mining - Zejun Liu; Yingying Lin; Yanhong Ge; Ziyue Zhu; Jinlong Yuan; Qidong Yin; Bingjun Liu; Kai He; Maochuan Hu (Journal of Environmental Management, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Elucidation of mechanisms, pathways, and toxicity of fabricated Z-scheme KNbO3/ZnIn2S4 hollow core–shell composites for enhanced ciprofloxacin photodegradation - Zuming He; Kai Lin; Ngie Hing Wong; Jaka Sunarso; Yongmei Xia; Xiaofei Fu; Jiangbin Su; Zhengyi Huang; Yong Wang; Bin Tang (Chemical Engineering Journal, 2023)

Phytochemistry and biological activities of corynanthe alkaloids - Jun Li; Jia-Xing Li; Hua Jiang; Min Li; Lin Chen; Yue-Yue Wang; Lu Wang; Ning Zhang; He-Zhe Guo; Kai-Long Ma (Phytochemistry, 2023)

Copper nanoparticles encapsulated in reduced graphene oxide electrode (CuxrGO1-x) for the electrochemical quantification of metformin in water - Yu-Jen Shih; Yu-Qiao Su; Wei-Hsiang Chen; Sheng-Kai Lin; Yi-Chun He; Chin-Pao Huang (Chemical Engineering Journal, 2023)

Holocene climatic controls on flooding regime along the Ussuri River in Northeast Asia - Zhenqing Zhang; Lin Li; Rui Yin; Lu Zhang; Kai Yi; He Ji; Haijiao Yin; Lili Huo (Science of The Total Environment, 2023)

Effects of phosphorus fertilizer application rate on transformation processes of phosphorus fractions in the purple alluvial soil of a riparian zone - Li-ping He; Kai-tao Jia; Dan Liu; Ke-hong Wang; Lin-Yan Duan; Jun-jie Lin (Journal of Mountain Science, 2023)

Carbon quantum dot fluorescent probe for labeling and imaging of stellate cell on liver frozen section below freezing point - Yan-Fei He; Kai Cheng; Zi-Tao Zhong; Xiao-Lin Hou; Chang-Zhi An; Jing Zhang; Wei Chen; Bo Liu; Jing Yuan; Yuan-Di Zhao (Analytica Chimica Acta, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Liver Organoids, Novel and Promising Modalities for Exploring and Repairing Liver Injury - Chiyu He; Di Lu; Zuyuan Lin; Hao Chen; Huigang Li; Xinyu Yang; Modan Yang; Kai Wang; Xuyong Wei; Shusen Zheng; Xiao Xu (Stem Cell Reviews and Reports, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

Aloe polysaccharide promotes osteogenesis potential of adipose-derived stromal cells via BMP-2/Smads and prevents ovariectomized-induced osteoporosis - Xue-wei Yao; He-dong Liu; Mao-xian Ren; Tian-lin Li; Wen-kai Jiang; Zhi Zhou; Zhi-yi Liu; Min Yang (Molecular Biology Reports, 2022)
Background Aloe polysaccharide (AP) is a type of an active macromolecule of Aloe vera, which contributes to its function. However, whether AP possesses anti-osteoporosis properties is unknown. Methods Adipose-derived stromal cells were treated with different concentrations of AP. Early and late osteogenesis were, respectively, evaluated by ALP and Alizarin Red S staining. The effect of AP on the processes of adipogenesis inhibition in ADSCs was analyzed by oil red O staining. Western blot was used to assess the expression of osteogenic and adipogenic related factors. Then, Noggin was administered to further confirm the mechanism by which AP promotes the osteogenesis of ADSCs. Finally, 40 female SD rats were classified into a bilateral laparotomy group (Sham group) and three bilateral ovariectomy groups: OVX group, OVX + AP group, and OVX + AP + Noggin group. The bilateral rat femurs were collected to perform micro-CT scanning, HE, Masson trichrome, and Oil red O staining. Results The results indicated that AP could increase ALP expression and calcium deposition. Through molecular mechanisms, AP promotes the protein expression of COL1A1, OPN, and ALP in ADSCs, but downregulates the expression of PPARγ. Also, AP directs ADSCs’ fate by stimulating the BMP2/Smads signaling pathway. In vivo, the rat AP-treated had more trabecular bone than the OVX rat, indicating partial protection from cancellous bone loss after treatment with AP. Conclusion Our results show that AP may promote osteogenesis of ADSCs through BMP-2/Smads signaling pathway and inhibits lipogenic differentiation. Thus, AP might be a promising alternative medicine to treat postmenopausal osteoporosis.

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Two new physalins from Physalis alkekengi L. var. franchetii (Mast.) Makino - Jia-Min Sun; Ji-Xiang He; Min Huang; Hui-Xin Hu; Lin-Tao Xu; Kai-Li Fang; Xiao-Ning Wang; Tao Shen (Natural Product Research, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Extracellular histones induce inflammation and senescence of vascular smooth muscle cells by activating the AMPK/FOXO4 signaling pathway - Hang Yang; Yong-Yan Luo; Lue-Tao Zhang; Kai-Ran He; Xiao-Jun Lin (Inflammation Research, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Characterization of physicochemical parameters and bioavailable heavy metals and their interactions with microbial community in arsenic-contaminated soils and sediments - Guobing Lin; Kai Wang; Xiaoman He; Zhaoguang Yang; Lin Wang (Environmental Science and Pollution Research, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Algae, shrimp grazing, and fecal pellets synergistically increase microbial activity and enhance N immobilization during Typha angustifolia leaf litter decomposition - Xiangshi Kong; Can Wu; Bei Yao; Zaihua He; Hong Lin; Xingbing He; Yonghui Lin; Tingting Cao; Yanyan Jia; Yongfei Li; Kai Tian; Xingjun Tian (Environmental Science and Pollution Research, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Streptomyces luteolifulvus sp. nov., a novel actinomycete isolated from soil in Nanjing, China - Shanshan Zhao; Ming Cheng; Congyu Lin; He Liu; Zhengran Wang; Kai Zhang; Simin Song; Qian Yang (Antonie van Leeuwenhoek, 2021)

An eco‐city design methodology for hilly areas of western China - Kai Lin; Zhengwei He; Zhujun Zhao; Jiaxin Chang; Keran Tang; Rui Qu; Li He (Earth Science Informatics, 2021)

Geographic modeling and simulation systems for geographic research in the new era: Some thoughts on their development and construction - Min Chen; Guonian Lv; Chenghu Zhou; Hui Lin; Zaiyang Ma; Songshan Yue; Yongning Wen; Fengyuan Zhang; Jin Wang; Zhiyi Zhu; Kai Xu; Yuanqing He (Science China Earth Sciences, 2021)
Regionality, comprehensiveness, and complexity are regarded as the basic characteristics of geography. The exploration of their core connotations is an essential way to achieve breakthroughs in geography in the new era. This paper focuses on the important method in geographic research: Geographic modeling and simulation. First, we clarify the research requirements of the said three characteristics of geography and its potential to address geo-problems in the new era. Then, the supporting capabilities of the existing geographic modeling and simulation systems for geographic research are summarized from three perspectives: Model resources, modeling processes, and operational architecture. Finally, we discern avenues for future research of geographic modeling and simulation systems for the study of regional, comprehensive and complex characteristics of geography. Based on these analyses, we propose implementation architecture of geographic modeling and simulation systems and discuss the module composition and functional realization, which could provide theoretical and technical support for geographic modeling and simulation systems to better serve the development of geography in the new era.

Identification of progranulin as a novel diagnostic biomarker for early-onset sepsis in neonates - Kai-Di Yang; Yu He; Sa Xiao; Qing Ai; Jia-Lin Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Impact of Maternal Separation on Dopamine System and its Association with Parkinson's Disease - Kai-jie He; Yu-ting Zhang; Shi-zhuang Wei; Shu-min Jiang; Lin Xu; Chao Ren; Fen Wang (NeuroMolecular Medicine, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Daily minimum temperature and precipitation control on spring phenology in arid‐mountain ecosystems in China - Jun Du; Kai Li; Zhibin He; Longfei Chen; Pengfei Lin; Xi Zhu (International Journal of Climatology, 2020)
Climate anomaly has caused substantial shifts in phenology of mountain ecosystems, but the underlying mechanism of phenological responses to climate change is still not well understood. In essence, the abundance of vegetation communities increases the complexity of phenology‐climate relationships, leading to a certain limitation in predictions of future dynamics among different vegetation types using a unified model. In this study, we focused on the climatic constraints on spring phenology in arid mountains (AMs) of China, and emphasis was laid on accurate representation of mechanisms that control phenology across different vegetation types. We Firstly explored spatio‐temporal variations in satellite‐derived estimates of starting date of vegetation growing season (SOS) over the period 2000–2015 using moderate‐resolution imaging spectro‐radiometer (MODIS) normalized difference vegetation index (NDVI). Phenological models in response to climate variability were then established by using mixed‐effect models based on satellite observations and an extensive dataset of climatic measurements. Our results showed that the climatic regulation on SOS varied greatly over vegetation types. More climatic factors that regulate phenological development were found in grassland than forest and shrubland. At ecosystem level, two critical climate factors, daily minimum temperature ( T min ) and precipitation, explained 74–95% of total variability in predicted SOS. The observed sensitivity to T min is expected to be closely linked with the risk of frost damage, while preseason precipitation determines water availability in spring. The varying ecosystem sensitivity revealed the different resilience and adaptability to changing climate among vegetation types, which have been linked to their eco‐physiological characteristics (e.g., water use efficiency) and environmental conditions (e.g., elevation). Overall, our results indicate a strong dependence of spring phenology on T min and precipitation, and create an opportunity for a more realistic representation of vegetation phenology and growth of AM plants in China in land surface models.

Priming effect of litter mineralization: the role of root exudate depends on its interactions with litter quality and soil condition - Kai Tian; Xiangshi Kong; Liuhuan Yuan; Hong Lin; Zaihua He; Bei Yao; Yanli Ji; Junbo Yang; Shucun Sun; Xingjun Tian (Plant and Soil, 2019)

Correction to: Efficient removal of dyes from dyeing wastewater by powder activated charcoal/titanate nanotube nanocomposites: adsorption and photoregeneration - Yingchao Lin; Jun Ma; Wen Liu; Zeyu Li; Kai He (Environmental Science and Pollution Research, 2019)

Efficient removal of dyes from dyeing wastewater by powder activated charcoal/titanate nanotube nanocomposites: adsorption and photoregeneration - Yingchao Lin; Jun Ma; Wen Liu; Zeyu Li; Kai He (Environmental Science and Pollution Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Local root status: a neglected bio-factor that regulates the home-field advantage of leaf litter decomposition - Kai Tian; Xiangshi Kong; Jianguo Gao; Yanyan Jia; Hong Lin; Zaihua He; Yanli Ji; Zhanlin Bei; Xingjun Tian (Plant and Soil, 2018)

Cyproheptadine Regulates Pyramidal Neuron Excitability in Mouse Medial Prefrontal Cortex - Yan-Lin He; Kai Wang; Qian-Ru Zhao; Yan-Ai Mei (Neuroscience Bulletin, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Co-expression of the C-terminal domain of Yersinia enterocolitica invasin enhances the efficacy of classical swine-fever-vectored vaccine based on human adenovirus - Helin Li; Pengbo Ning; Zhi Lin; Wulong Liang; Kai Kang; Lei He; Yanming Zhang (Journal of Biosciences, 2015)

AVO forwarding modeling in two-phase media: multiconstrained matrix mineral modulus inversion - Kai Lin; Zhen-Hua He; Xiao-Jun Xiong; Xi-Lei He; Jun-Xing Cao; Ya-Juan Xue (Applied Geophysics, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Flammeopellis bambusicola gen. et. sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and phylogenetic analysis - Chang-Lin Zhao; Xin-Sheng He; Kun-Yuan Wanghe; Bao-Kai Cui; Yu-Cheng Dai (Mycological Progress, 2014)

FGF21 inhibits apolipoprotein(a) expression in HepG2 cells via the FGFR1-ERK1/2-Elk-1 pathway - Xiaolong Lin; Guohua Li; Xinglan He; Xiaofeng Ma; Kai Zhang; Hai Zhang; Gaofeng Zeng; Zuo Wang (Molecular and Cellular Biochemistry, 2014)

Neuronal and Astroglial TGFβ-Smad3 Signaling Pathways Differentially Regulate Dendrite Growth and Synaptogenesis - Chuan-Yong Yu; Wei Gui; Hui-Yan He; Xiao-Shan Wang; Jian Zuo; Lin Huang; Nong Zhou; Kai Wang; Yu Wang (NeuroMolecular Medicine, 2014)

Iron Overload Inhibits Osteoblast Biological Activity Through Oxidative Stress - Yin-Feng He; Yong Ma; Chao Gao; Guo-yang Zhao; Lin-Lin Zhang; Guang-Fei Li; Yun-Zhi Pan; Kai Li; You-Jia Xu (Biological Trace Element Research, 2013)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

High-precision frequency attenuation analysis and its application - Xiao-Jun Xiong; Xi-Lei He; Yong Pu; Zhen-Hua He; Kai Lin (Applied Geophysics, 2011)

Self-adapting extraction of matrix mineral bulk modulus and verification of fluid substitution - Kai Lin; Xiao-Jun Xiong; Xiao Yang; Zhen-Hua He; Jun-Xing Cao; Xi-Hua Zhang; Ping Wang (Applied Geophysics, 2011)

BAK1 and BKK1 in Arabidopsis thaliana confer reduced susceptibility to turnip crinkle virus - Hui Yang; Xiaoping Gou; Kai He; Dehui Xi; Junbo Du; Honghui Lin; Jia Li (European Journal of Plant Pathology, 2010)